Oxygen uptake during local vibration and cycling - Sperlich, B.; Kleinöder, H.; de Marees, M.; Quarz, D.; Mester, J. (Science and Skiing IV, 2008)
INTRODUCTION: In cross country skiing, cycling and whole Vibration (vib) are exercised to enhance endurance and strength. In order to have both effects we developed a vib-cycle prototype in which only the bottom crank is fixed on a vib. platform (Patent No.: DE 102004063495). The frame is physically disconnected from any vib Stimulus reducing the shock waves to the lower body's muscles referring to as local vib. The aim of the study was to evaluate whether dynamic vib Stimulus increases oxygen uptake (V"O2).